2023
DOI: 10.1111/jgh.16212
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of robot‐assisted versus laparoscopic surgery for colorectal cancer in morbidly obese patients: A propensity score‐matched analysis of the US Nationwide Inpatient Sample

Abstract: Background and AimMorbid obesity is associated with poorer postoperative outcomes in colorectal cancer (CRC) patients. We aimed to evaluate short‐term outcomes after robotic versus conventional laparoscopic CRC resection in morbidly obese patients.MethodsThis population‐based, retrospective study extracted data from the US Nationwide Inpatient Sample during 2005–2018. Adults ≥ 20 years old, with morbid obesity and CRC, and undergoing robotic or laparoscopic resections were identified. Propensity score matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Since the advent of robotic assistance in colorectal resections, multiple studies have been done comparing post-operative outcomes of robotic colorectal resections (RCR) versus laparoscopic colorectal resections (LCR). Some have shown that RCR is superior to LCR ( 12 , 13 ). A network meta-analysis done by Seow et al showed that RCR offers better distal resection margin distance and a shorter length of hospital stay ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the advent of robotic assistance in colorectal resections, multiple studies have been done comparing post-operative outcomes of robotic colorectal resections (RCR) versus laparoscopic colorectal resections (LCR). Some have shown that RCR is superior to LCR ( 12 , 13 ). A network meta-analysis done by Seow et al showed that RCR offers better distal resection margin distance and a shorter length of hospital stay ( 14 ).…”
Section: Introductionmentioning
confidence: 99%